Crohn’s disease in coastal China: epidemiological profile and determinants of diagnostic delay in the Yancheng cohort - Jin, Shengnan; Zhang, Maozhen; Zhou, Zixuan; Hao, Yanping; Wang, Lin; Xu, Su (Frontiers in Physiology, 2025)
Background and aimsCrohn’s disease (CD) exhibits escalating incidence in China, particularly in coastal regions undergoing rapid industrialization. We aim to investigate the epidemiological characteristics of CD and identify factors influencing diagnostic delay in the Yancheng region of China.MethodsA cross-sectional analysis was conducted on CD patients from two tertiary medical centers (Yancheng TCM Hospital Affiliated to Nanjing University of Chinese Medicine and Yancheng No.1 People’s Hospital) between October 2021 and October 2024. We calculated crude prevalence and incidence rates, and performed logistic regression analyses to identify predictors of diagnostic delay.ResultsAmong 200 enrolled CD patients (male-to-female ratio: 2.07:1), the crude prevalence and incidence rates were 17.48/100,000 and 2.3/100,000, respectively. Diagnostic delay occurred in 48% (96/200) of cases, with a median delay duration of 23 months (IQR: 12–48; maximum: 300 months). Multivariate analysis identified advanced age at diagnosis as an independent risk factor for delay (OR = 1.035, 95% CI: 1.010–1.060, P = 0.005), while abdominal pain served as a protective factor (OR = 2.088, 95% CI: 1.136–3.838, P = 0.018). Diagnostic delay duration correlated positively with age at diagnosis (r = 0.302, P = 0.003) and frequency of refrigerated food consumption (r = 0.219, P = 0.032). No significant associations were observed between delay duration and complications such as intestinal obstruction, perforation, or surgical intervention (P > 0.05).ConclusionThe Yancheng region exhibits higher CD prevalence and incidence rates compared to national averages, with pronounced diagnostic delays. These findings highlight the need for targeted interventions to improve early diagnosis and mitigate healthcare burdens.